On the mesoscale fracture initiation criterion of heterogeneous steels during quenching - Said Schicchi, D. (2017)
A numerical model aimed at investigating the microcracking behavior in steel meso-structures during quenching process is proposed in this work. The proposal explicitly considers the material heterogeneity influencing the fracture response of the steel meso-specimen under consideration. Particularly, a finite element based model is used in a two-stage simulation: (i) the first stage deals with solving the coupled metallo-thermo-mechanical problem at macroscopic level during quenching; (ii) the second stage accounts for the mesoscopic cracking based on a discontinuous approach by means of the extended finite element method. Different strain and stress histories have been used as failure (initation) criteria and have been compared with experimental results on high speed quenching of a 100Cr6 cylindrical (SAE 52100) steel specimen. The good agreement between the numerical simulations, adopting a maximum principal stress criterion as cracking initiation rule, and the experimental results indicates the potential of the presented methodology in the failure prediction.